EFFECTS OF DEFOLIATION AND NITROGEN UPTAKE ON FORAGE NUTRITIVE VALUES OF PENNISETUM SP - M. P. Palacios-Díaz; V. Mendoza-Grimón; J. R. Fernández-Vera; J. M. Hernández-Moreno (Journal of Animal and Plant Sciences, 2013)
In semiarid regions, the increasing cost of imported forage is encouraging its replacement by on-farm produced fodder crops. The aim of this study was to characterize the nutritive values of maralfalfa grass ( Pennisetum sp.) in function of different harvest frequencies under subsurface drip irrigation. During 2009 a maralfalfa grass experiment was conducted 2 in a field of 8000 m on allophanic soils in the island of Hierro (Canary Islands), under subtropical climate. In a randomized block design, one linear meter from three different rows was sampled of plants from 30 to 120 days. In a 50 2 m subplot, biodegraded liquid pig manure was applied. Crude Protein (CP) in plants was determined with and without it. Another objective was to calculate N uptake which was added by manure and, the N depletion in soil in organic farming production. The results showed that the optimum age for harvesting was 55-60 days and also allowed to obtain relationships between CP and the age of the plant. Our results demonstrate that, in order to obtain high yields of -1 -1 maralfalfa by organic farming, the maximum animal residue use of 240 kg N ha year recommended by the European Community Directive 91/676/EEC should be increased. alternative to increase forage availability for livestock
Keywords: crude protein; drip irrigation; Maralfafa ( Pennisetum sp); N uptake; N depletion; organic farming